Financial Literacy and Lifestyle Mediated by Financial Technology on Generation Alpha’s Money Ethic Perspective - Afni Sirait; Anake Nagari; Siti Rokhimah; Crescentiano Agung Wicaksono (AIBPM Publisher, 2025)
Today, the fulfillment of daily needs can be assisted using technology. This technological advancement is also in line with changes in the habits of today's society who really want everything to be fast and instant, one of which is Generation Z. This research uses quantitative methods with 90 Generation Z respondents. Data collection was carried out using a questionnaire, then testing validity, reliability, and evaluating the model structure using the SmartPLS 4.0.0 data analysis tool. The data that has been processed and analyzed explains that there is a direct relationship between Financial Literacy and Money Ethic (P Value 0.005; T-Statistic 2.807). The mediating variable added to the Financial Literacy and Money Ethic variables has an insignificant effect (P Value = 0.766; T-Statistic = 0.298) so that the lifestyle variable provides a full mediating effect. The results of testing Financial Technology with Money Ethic found no direct relationship (P = 0.057; T-Statistic = 1.907) and the indirect relationship through the lifestyle mediation variable was not significant (P = 0.075; T-Statistic = 1.779) so that the variable did not mediate. While the relationship of Lifestyle analysis results to Money Ethic is significant (P=0.022; T-Statistic = 2.291). This research is expected to provide benefits for researchers in the field of behavioral accounting, especially observations based on generation specifications).